Spectrophotometric method of estimation of atorvastatin calcium using sulfo-phospho-vanillinreaction - Shyni Bernard, Molly Mathew (Journal of Applied Pharmaceutical Science)
A simple and sensitive visible spectrophotometric method has been developed for the determination of Atorvastatin (ATV) in pure form and in tablets using Sulfo-Phospho-Vanillin reagent.The methods is based on the reaction of atorvastatin with sulphuric acid to form carbonium ion,which subsequently react with vanillin phosphate ester and measuring the resulting purple coloured complex at 414 nm. Under the proposed optimum condition, Beer’s law was obeyed at the concentration range of 30-100μg/ml. The result of analysis of tablet was found to be 99.81 %. The good results of recovery studies showed that the co-formulated substances did not interfere with the determination. The method was validated according to ICH guidelines by performing linearity, accuracy, and precision, limits of quantification, limit of detection and selectivity.
Keywords: Atorvastatin,Spectrophotometry,Tablets,Vanillin.